Analgesic use, pain and daytime sedation in people with and without dementia in aged care facilities: a cross-sectional, multisite, epidemiological study protocol. Issue 6 (19th June 2014) - Tan, Edwin C K; Visvanathan, Renuka; Hilmer, Sarah N; Vitry, Agnes I; Quirke, Tara; Emery, Tina; Robson, Leonie; Shortt, Terry; Sheldrick, Simon; Lee, Sunny (Soon Won); Clothier, Robyn; Reeve, Emily; et al.
Abstract : Introduction: People living with dementia may experience and express pain in different ways to people without dementia. People with dementia are typically prescribed fewer analgesics than people without dementia indicating a potential difference in how pain is identified and treated in these populations. The objectives of this study are to (1) investigate the prevalence of analgesic load, pain and daytime sedation in people with and without dementia in Australian residential aged care facilities (RACFs), and (2) investigate the clinical and diagnostic associations between analgesic load, pain and daytime sedation in people with and without dementia in Australian RACFs. Methods/analysis: This will be a cross-sectional study of 300 permanent residents of up to 10 low-level and high-level RACFs in South Australia with and without dementia. Trained study nurses will administer validated and dementia-specific assessments of self-reported and clinician-observed pain, sedation and other clinical and humanistic outcomes. Medicine-use data will be extracted directly from each resident's medication administration chart. Binary and multinominal logistic regression will be used to compute unadjusted and adjusted ORs and 95% CIs for factors associated with pain, analgesic load and daytime sedation. These factors will include dementia severity, behavioural and psychological symptoms, quality of life, resident satisfaction, attitudes towards medicines, activities of daily living and nutritional status. Ethics and dissemination: Institutional ethics approval has been granted. The findings will be disseminated through public lectures, professional and scientific conferences and in peer-reviewed journal articles. The findings of this study will allow for a better understanding of the prevalence and factors associated with analgesic use, pain and other outcomes in residential care. The findings of this study will be used to inform the development and implementation of strategies to improve the quality of life of people with dementia.